Bagian Depan Agrotrop : Journal on Agriculture Science Vol. 13, No. 2, Mei 2023 - AGROTROP, Pengelola (Agrotrop : Journal on Agriculture Science; Vol 13 No 2 (2023), 2023)
Bagian Depan Agrotrop : Journal on Agriculture Science Vol. 13, No. 2, Mei 2023